Hypoxia Induced Infertility in Males: Role of Transcription Factor Hypoxia Inducible Factor -1 Alpha - Aasma Zaidi, Zaheer Iqbal Sheikh, Afsheen Akbar, Shaheena Naz, Shazia Ramzan, Faiza Habib (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To assess concentrations of HIF-1 α and correlation between HIF-1 α in healthy and sub fertile males’ population in our study. Methodology: In this study we investigated the concentrations of Hypoxia Inducible Factor 1-α (pg/mL) in the seminal plasma of healthy fertile males and sub fertile males using Enzyme-Linked ImmunoSorbent Assay (ELISA). Our study population (n=54) consisted of healthy fertile controls (n=18), sub fertile males without varicocele (n=22) and sub fertile males with varicocele. Result: Our results showed significantly (p <0.001) elevated levels of HIF 1-α in both sub fertile groups (p< 0.001) as compared to healthy fertile group. A significant (r= 0.975, p<0.001) positive correlation was noticed between the concentrations of Caspase 3, an apoptotic marker and HIF 1-α in the healthy fertile and sub fertile groups. Conclusions: Our study results suggest that hypoxia induced apoptosis maybe an important factor in causing testicular dysfunction in sub fertile males. In conclusion HIF 1-α is an important hypoxic factor that can be used to predict apoptosis in testes. HIF 1-α can be used as a clinical marker that can facilitate scientists to predict the degree of apoptosis in spermatozoa.